Geografia inclusiva na produção de material sensorial de escala geográfica para estudantes com Transtorno do Espectro Autista (TEA) dos anos finais do ensino fundamental - Guaresi, Yazana (2024)
The present work stems from observation and reflection on the increase in the number of students with Autism Spectrum Disorder (ASD) observed in classrooms and how Geography, as a school subject, can be inclusive and enable students with ASD to perceive themselves as individuals in this space of our school coexistence - the classroom - but above all, in different portions and sharings of the geographic space. The main objective of the work is to construct a sensory material of geographic scale for students with Autism Spectrum Disorder (ASD) in the Final Years of Elementary School, in the curricular component of Geography, in order to contribute to their development of perception as subjects within the categories of analysis of the geographic scale. Thus, the specific objectives consist of reflecting on school Geography; differentiating cartographic and geographic scales; understanding perception within Geography; characterizing the origin of Special Education; as well as differentiating it from inclusive education; presenting Autism Spectrum Disorder (ASD) and reporting on sensory sensitivity in people with ASD; to discuss Inclusive Geography and analyzing scientific productions involving the teaching of Geography and students with ASD, and finally, constructing and applying the pedagogical product. Methodologically, the present research was anchored in a qualitative approach of the participant observation type, in which, as a teacher, I am inserted in the area to be researched for this work: the classroom of a public school; and I actively participate in what is researched - school Geography and the student with Autism Spectrum Disorder in the Final Years of Elementary School. The proposed final product is a sensory material of geographic scale for students with ASD, produced in different materials, which allows identification, perception, and scalar transit in nine fields of analysis, in the following course: 1) The "self," 2) Home, 3) Neighborhood, 4) Municipality, 5) Federative State, 6) Region (treated from the division proposed by IBGE in 1970, with changes resulting from the Constitution of 1988), 7) Country, 8) Continent, 9) Globe and the other continents of the Earth. This study seeks reflections on classroom work - as a teacher - aiming to contribute to the development of social processes, learning, and inclusion of students with ASD, so that Geography enables them to perceive themselves as subjects in the world.